The Moral Imperative: Protecting Children’s Welfare in Research and Experimental Therapies - Nsitem, Chimele (Journal of Student Research, 2024)
Charlie Gard, an 11-month-old baby who passed away in 2017, sparked international debate surrounding his battle with mitochondrial depletion syndrome, a rare terminal illness that lacks a cure (BBC, 2017; Nogueira et al., 2014). Burdened with progressive brain damage and muscle weakness, Charlie required a ventilator to breathe. After his story was publicized, Dr. Michio Hirano suggested that an experimental treatment involving nucleoside bypass therapy - aiming to restore Charlie’s ability to synthesize mitochondrial DNA by supplementing his body with naturally occurring compounds it couldn’t produce - may, in theory, benefit Charlie (Amtamm et al., 2023). However, ethical questions surfaced as the treatment had never been tried in a human or animal subject with mitochondrial depletion syndrome, prompting a deeper exploration into the ethical implications involving the pediatric population in research studies and experimental treatments. This controversial narrative underscores the ethical considerations surrounding health research regulations concerning human, specifically pediatric, subjects.